INTEGRATED NETWORK SYSTEM SECURITY TO DETERMINE GIS (GEOGRAPHIC INFORMATION SYSTEM) BASED CYBER CRIME PATTERNS - Dely Indah Sari; Muhammad Jufri (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: crime mapping, namely by examining various spatial data factors that can be integrated to be able to produce a variety of information for security officers and the government in an effort to realize security in an area by utilizing geographic information systems by mapping, visualizing and analyzing crime incidents so that Various patterns and trends of spatial and temporal crime are generated using the main concept of cryptography, namely the encryption or encryption process where the plaintext encoding process becomes ciphertext and the decryption or description process, which is the process of returning the ciphertext to the original plaintext using the Electronic Code Book (ECB) algorithm and the ECB algorithm vigenere Keywords: criminal patterns, geographic information systems, network system Abstrak: pemetaan kriminalitas yaitu dengan mengkaji berbagai macam faktor data spasial yang dapat terintegrasi untuk dapat menghasilkan keanekaragaman informasi bagi aparat keamanan dan pemerintah dalam upaya mewujudkan kemanan di suatu area dengan memanfaatkan sistem informasi geografis dengan cara dilakukan memetakan, memvisualkan dan menganalisis insiden kriminalitas sehingga dihasilkan beragam pola maupun trend kriminalitas secara spasial temporal dengan menggunakan konsep utama dari kriptografi yaitu proses enkripsi atau enkription dimana proses penyandian plainteks menjadi  cipherteks dan proses dekripsi atau description yaitu proses mengembalikan cipherteks menjadi plainteks semula menggunakan algoritma Elektronic Code Book (ECB) dan algoritma Vigenere. Kata kunci: pola kriminalitas, sistem informasi geografis, sistem keamanan